Uji Efektivitas Sistem Aerasi dan Dosis Vermikompos Terhadap Pertumbuhan dan Hasil Tanaman Baby Kailan (Brassica oleracea L var. acephala) Varietas New Veg-Gin pada Hidroponik Sistem Wick. - Agung Dwi Julianto; Rommy Andhika Laksono; Rika Yayu Agustini (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2021)
This research aims to determine the effect of the interaction between aeration and vermicompost on the growth and yield of baby kailan (Brassica oleracea L var. aceplaha) New Veg-Gin varieties on hydroponics of wick system. Experiment was carried in Kepuh, Karangpawitan Village, Karawang, West Java, from July to September 2020. The research method used is an experimental method using a factorial randomized block design. There are two factors of 10 treatments. First factor is aeration which of 2 levels, A0 (non aerated) and A1 (aerated). The second factor was dose of vermicompost nutrition which consisted 5 levels, P0 (AB mix), P1 (10ml), P2 (20ml), P3 (30ml), and P4 (40ml). Each treatment repeated 3 times so there were 30 units. Effect of treatment in analysis of variety and if F test at 5% level significant, then continued DMRT test at 5% level. The results of the experiment showed that there was no interaction between the provision of aeration system treatment level and vermicompost dosing on the growth and yield of baby kailan plants. A0 gave the highest yield on plant fresh weight 10.61 g. P1 gave the highest yield of 9.88 g plant fresh weight, which was not significantly different from other vermicompost doses.